Kinky choices, dictators and split might: a non-cooperative model for household consumption and labor supply - Jan Boone; Karen van der Wiel; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2009)
It is unlikely that husbands and wives always agree on exactly what public goods to buy. Nor do they necessarily agree on how many hours to work with obvious consequences for the household budget. We therefore model consumption and labor supply behavior of a couple in a non-cooperative setting by adopting a Nash approach. Using minimal assumptions, we prove that demand for public goods is characterized by three regimes. It is either determined by the preferences of one of the partners only (Husband Dictatorship or Wife Dictatorship), or by both spouses' preferences where a partner's influence depends on the spouses' relative wage rates (Split Might). These regimes imply a kinked nature of the couple's aggregate demand curves. By imposing more structure on the model, we can derive testable implications on observed demand for public goods and labor supply that allow testing the model against the standard unitary model where a couple behaves as a single decision maker. The model is applied to a sample drawn from the Consumer Expenditure Survey (CEX) whereby we explicitly focus on expenses on children's goods that act as a public good in the spouses' preferences. We find that for couples with two or three children the standard unitary model is strongly rejected in favor of our non-cooperative model. Moreover, it turns out that for the majority of these couples, there is a Wife Dictatorship in the sense that the spending pattern is according to her preferences.
urn:nbn:de:101:1-2009082010
Keywords: D11; D12; D13; 330; Consumption; labor supply; intra-household allocation; non-cooperative model; public goods; Öffentliches Gut; Konsumentenverhalten; Arbeitsangebot; Privater Haushalt; Gleichberechtigung; Hausarbeit; Nash-Gleichgewicht; Nichtkooperatives Spiel; Konsumtheorie; Theorie